Cymbopleura laszlorum spec. nov. (Cymbellaceae, Bacillariophyceae), a glacial relic from a calcium-rich floodplain fen in southwestern Montana, USA - Bahls, Loren; Luna, Tara (Phytotaxa, 2018)
Cymbopleura laszlorum is described using LM and SEM microscopy from a recently rehabilitated floodplain fen in southwestern Montana, USA. The new species is most similar to C. mongolica and C. stauroneiformis and shares features with several other northern/alpine species. Cymbopleura laszlorum lives in cold, calcareous, spring-fed pools where it is associated with Mastogloia lacustris, Cymbopleura florentina and Epithemia argus. The fen also supports three rare vascular plants that have northern/alpine affinities. These diatom and vascular plant associates and the close morphological resemblance of C. laszlorum to C. mongolica and C. stauroneiformis suggest that the new species is a glacial relic and survives at the type locality because it has retained the muskeg-like conditions that were more widespread during the last glacial period. Wetland habitats that support rare species of vascular plants are also likely to support new and rare species of diatoms.